KEEPING A PROMISE IS A SIGN OF TRUE HUMANITY (Universal International Scientific Journal, 2026)
This article emphasizes the importance of keeping promises and fulfilling every word given. It also emphasizes that keeping promises is not only a personal duty, but also a duty to society. Because, it is argued, if mutual trust is lost in society, the very foundation of humanity will be undermined.
Keywords: Promise, word, straightforwardness, generosity, goodness and virtue, generosity, generosity, controlling anger, zakat, relatives, family members, charity, kindness, friendship, loyalty, courage, humility, supreme kindness.